Delayed Diagnosis of Unilateral Mandibular Condylar Fracture in a Posterior Edentulous Patient - Sahani Anupama; Pilana Vithanage Kalani Shihanika Hettiarachchi (Case Reports in Dentistry)
Background. Fractures of the mandible are common in elderly patients, and among them, condylar fractures are the most frequent type. A change in occlusion is the most common physical finding in patients with fractures of the mandible. Therefore, it is challenging to identify mandibular fractures in posterior edentulous patients due to the lack of posterior occlusal contacts. It is crucial to do radiological investigations in such patients to exclude fractures. Case Presentation. This article describes a case of delayed diagnosis of a unilateral mandibular condylar fracture for a week’s duration and treating the condition as temporomandibular pathology in a posterior edentulous, 52-year-old patient. Conclusion. This clinical case highlights the importance of radiological investigations and occlusal analysis for early diagnosis of condylar fractures, particularly in posterior edentulous patients, lacking posterior occlusal contacts.